Enhancement of Nano Catalyst for an Alkaline Fuel Cells - Haleemah J. Mohammed; Nathera A. Ali (University of Thi-Qar Journal of Science, 2020)
An alkaline fuel cell, which was developed using nano catalyst (Pt:CNTs) for electrodes. Study has been prepared (Pt:CNTs) nano catalyst, The Structural characteristics were studied through the analysis of X-ray diffraction (XRD) of the prepared nano catalyst for determining the yielding phase and Scanning Electron Microscope (SEM), were used to characterize, Mesh stainless steel catalyst substrate had an envelope structure and a large surface area. In addition, study the characterization of the electrochemical parameters. Electrochemical modelling and nano catalyst led to optimization of cell voltage, current & power densities and the results are found to be 1.76 V, 3.9 A.